ANALISIS PENGARUH KEPERCAYAAN MERK TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA KONSUMEN RETNO SKIN CAREDI SURAKARTA - Caturani, Erwin; Suseno, Y. Djoko; Widajanti, Erni (Universitas Slamet Riyadi, 2019)
This research (1) Analyze the significance of the influence of brand trust on the satisfaction of Retno Skin Care Consumers in Surakarta. (2) Analyze the significance of the influence of brand trust on the loyalty of Retno Skin Care Consumers in Surakarta. (3) Analyze the significance of the brand trust on the loyalty of Retno Skin Care Consumers in Surakarta. (4) Analyze the significance of the influence of brand trust on the loyalty by mediating customer satisfaction in Retno Skin Care Consumers in Surakarta.This research took the location of Retno Skin Care in Surakarta using a sample of 100 respondent of Retno Skin Care services users in Surakarta. How to take sample with questionnaires. Based on the result of testing each hypothesis shows that wich states â€œconsumer confidence has a significant effect on consumers loyaltyâ€ proved the truth. The third hyphotesis states that â€œconsumer satisfaction has a significant effect on customer loyalty by mediating consumer satisfaction in retno skin care consumers in Surakartaâ€, proven true.